Rogue One : a Star Wars story [videorecording (Blu-Ray + DVD)] - Lucas, George, 1944- ([Walt Disney Studios Home Entertainment], 2017)
In a period of great conflict, a group of unlikely heroes led by Jyn Erso, a daring fugitive, and Cassian Andor, a rebel spy, band together on a desperate mission to steal the plans to the Death Star, the Empire's ultimate weapon of destruction.